Internal Quality Assurance Practices: The Case of Gondar University - Teshome, Samson Worku; H/Wold, Dawit Tefera; Aga, Firdissa Jebessa; Birru, Yonas Tefera (Darul Yasin Al Sys, 2025)
This study examines the internal quality assurance (IQA) practices at Gondar University, one of Ethiopia’s oldest and largest public universities. Despite its long history dating back to 1954 as a public health training institution, the university has faced challenges in institutionalizing a comprehensive Quality Assurance system. The establishment of the Education Quality Assurance and Audit Directorate (EQAAD) in 2003 marked a significant step towards formalizing Internal Quality Assurance processes. Through qualitative data collected via interviews and document analysis, this research explores the achievements, key focus areas, challenges, and gaps in the university's Quality Assurance framework. Among its accomplishments are the development of the Education Quality Improvement Package (EQIP), hosting national QA conferences, conducting graduate tracer studies, and implementing self-audits and program evaluations. However, the study reveals systemic challenges including limited staffing capacity, insufficient financial resources, inconsistent implementation of QA procedures, and minimal involvement of top management and academic staff in routine QA activities. Structural and procedural weaknesses such as unclear leadership roles, lack of reward mechanisms, and under emphasis on research and community engagement were also identified. The findings highlight the need for stakeholder engagement, policy innovation, and resource mobilization to strengthen the QA culture. The study concludes that while Gondar University has laid a foundation for quality enhancement, sustained institutional commitment is essential for meaningful improvement.